2006
DOI: 10.1042/cs20060049
|View full text |Cite
|
Sign up to set email alerts
|

Can angiogenesis be exploited to improve stroke outcome? Mechanisms and therapeutic potential

Abstract: Recent developments in our understanding of the pathophysiological events that follow acute ischaemic stroke suggest an important role for angiogenesis which, through new blood vessel formation, results in improved collateral circulation and may impact on the medium-to-long term recovery of patients. Future treatment regimens may focus on optimization of this process in the ischaemic boundary zones or 'penumbra' region adjacent to the infarct, where partially affected neurons exposed to intermediate perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 137 publications
(146 reference statements)
1
133
0
3
Order By: Relevance
“…31 However, angiogenesis alone would have less impact on repair, if the BBB is not restabilized. In this study, we present insights into the integral role of pericytes in the normal course of endogenous BBB recovery after cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, angiogenesis alone would have less impact on repair, if the BBB is not restabilized. In this study, we present insights into the integral role of pericytes in the normal course of endogenous BBB recovery after cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…36 Furthermore, angiogenesis is considered a key feature of ischemic stroke recovery and neuronal post-stroke re-organization. 37 Several studies using experimental stroke models have indicated the beneficial effects of glibenclamide administration after reperfusion, such as reversing ischemia-reperfusion injury by halting oxidative stress and inflammation in the hippocampus, 9 preventing cytotoxic edema after cerebral ischemia, 2,3,1,7 and enhancing neuroprotection, which all eventually lead to a better functional outcome. 8 Thus, although glibenclamide did not modify the size and cell density of microglia nor astroglia after ischemia here, it enhanced long-term brain repair processes and functional recovery outcomes of the rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other avenues of study are directed to the development of derivations of EPO to reduce erythropoietic activity and the potential associated vascular complications (Montero et al, 2007). Yet, these lines of investigation are not without limitations, since chemical derivatives of EPO can become absent of clinical efficacy as well as possibly lose the ability to promote sustainable cytoprotective effects, such as neurogenesis (Gonzalez et al, 2007) and angiogenesis Reinders et al, 2006;Slevin et al, 2006;Zhang and Ma, 2007).…”
Section: Future Perspectives and Considerations For Epomentioning
confidence: 99%